Examining the pharmacological and psychological treatment of child and adolescent ADHD in Australia: Protocol for a retrospective cohort study using linked national registry data. Issue 11 (23rd November 2022) - Sullivan, Daniel P; Payne, Leanne; Boulton, Kelsie A; Silove, Natalie; Bellgrove, Mark A; Sciberras, Emma; Coghill, David R; Guastella, Adam J; Middeldorp, Christel M
Abstract : Introduction: Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder which affects 5% of children globally. In Australia, it is estimated that 4.1% of children and adolescents have ADHD. While research has examined the treatment and outcomes of children with ADHD attending public mental health services during their time in the public system in Australia, it is not known what treatment they received before and after these treatment episodes, which will provide a more complete understanding of these children's treatment journey. Methods and analysis: We will link clinical data from cohorts of children and adolescents treated in the public child and youth mental health and/or child development services in Brisbane, Melbourne and Sydney to the Medicare Benefits Schedule (MBS), Pharmaceutical Benefits Scheme (PBS) and National Death Index. MBS data will demonstrate the treatment journey with respect to clinicians seen, and treatment episodes from the public health service data sets will be examined to assess if the type and intensity of treatment are related to treatment outcomes. PBS data will reveal all psychotropic medications prescribed, allowing an examination of not just ADHD medications, but also other psychotropics which may indicate co-occurring conditions (eg, anxiety and mood disorders). Statistical analyses will include descriptive statistics to describe the rates of specific medications and clinician specialties seen. Linear and logistic regression will be used to model how treatment and sociodemographic variables relate to routinely collected outcome measures in the public health system while controlling for covarying factors. Ethics and dissemination: This study has been approved by the following institutional ethics committees: (1) Children's Health Queensland Hospital and Health Service (HREC/21/QCHQ/76260), (2) The University of Queensland (2021/HE002143) and (3) The Australian Institute of Health and Welfare (EO2021/4/1300). Findings will be disseminated through peer-reviewed journals, conferences, professional associations and to public mental health services that treat ADHD.